Konstruksi Instrumen Tes Keterampilan Berpikir Kritis Siswa Pada Materi Suhu Dan Kalor Madrasah Aliyah Negeri 1 Batang Hari - Didit Prayogo; M. Junaid; Zainal Hartoyo (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2019)
This research was conducted to contruct the critical thinking test instrument for the students to facilitate the learning procces especially on the subject of physic. This study aims to get a picture of the characteristic of critical skills test thinking; quality of the test instrument is critical thinking; and the state of critical studenst thinking regarding temperature and heat matter. This research is a mixed method research strategy that involves the processe of collecting and analyzing data in one lesson.Sheet of essay validation, the observed aspects are material,construction and language. a collection methods used are test technique. Data analyst techniques used are quantitative descriptive analyst, qualitative descriptive analyst and descriptive stastistics analyst. The results of the study showed that (1) Instrument characteristic of students critical thinking skill test is made by ennis indicator tranlation (1966) namely basic clarification; basic in making desicions and support; inferece; Basic Clarification; strategy and tactic.The test instrumentMade is an essay with temperature and heat material.essay test is one form of written test. The composition consist of items of question items trough the description of words that reflect students thinking ability (2) the quality of the thinking skills test instrument is borrowed from the aspect of validity, distingualisting power, the level of ease and reability of the data analiyst show the good category.(3) stateofthe students thinking test skills identified critical thinking test obtained from the results of data analyst are categorized being with score of 69,25.